Race, Risk, and Recreation in Personal Genomics: The Limits of Play. - Lee, Sandra Soo‐Jin (Medical Anthropology Quarterly, 2013)
Despite the mantra that genetics has moved beyond race, the burgeoning industry of genetic ancestry reveals how genetics has offered new technology through which individuals can link to intersections in time and space in complex ways that recapitulate understandings of racial order, origins, and group membership. This article focuses on the trope of 'recreation' asserted in the marketing of ancestry genetic tests and examines the suggestion of self-discovery through the recovery of lost kin. Themes of recreation and re-creation paradoxically suggest both passivity of self-revelation and the power to re-act and re-create one's self in light of a different, more enlightened future. Direct-to-consumer personal genetics testing companies play guardian to this consumer play, providing tailored genetic scripts and highlighting how consumers might use their information. This article critically examines the play with concepts of ancestry, ethnicity, and genetic variation and their implications for public understanding of the relationship between race and genetics.